Comunità inclusive e gestione collettiva dei beni - Fabrizia Cesarano (Democrazia e Diritti Sociali)
The paper analyses various forms of collective management of assets, both those codified by Law No. 168/2017 and those that have emerged in both regulatory practices and local regulations concerning urban commons, such as collaboration pacts and self-governance models. The analysis begins with a constitutional reinterpretation of property rights, focusing on the function of assets in relation to the general interest and the active role of communities. The aim is to identify models capable of ensuring inclusive, accessible, and solidarity-based use of shared resources.